2017
DOI: 10.21873/anticanres.11695
|View full text |Cite
|
Sign up to set email alerts
|

Multiparametric MRI/TRUS Fusion Prostate Biopsy: Advantages of a Transperineal Approach

Abstract: Multiparametric MRI/TRUS TP in comparison to TR fusion biopsy detected a greater percentage of small but clinically significant PCa of the anterior zone (86.7% vs. 46.7%; p=0.0001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…We found 39 retrospective studies, 46 prospective studies, and 13 RCTs where periprocedural antibiotics were administered [12] , [13] , [14] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , …”
Section: Evidence Synthesisunclassified
“…We found 39 retrospective studies, 46 prospective studies, and 13 RCTs where periprocedural antibiotics were administered [12] , [13] , [14] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [67] , [68] , [70] , [71] , [72] , [73] , [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] , [82] , [83] , [84] , [85] , …”
Section: Evidence Synthesisunclassified
“…The multiparametric MRI-ultrasound fusion biopsy is currently an accepted modality in the pathological detection of prostate cancer [30]. In contrast to prostate cancer, little effort has been made for developing the ‘MRI-PDD fusion TURBT’ for the diagnosis and treatment of bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…48 -Seven studies reported on the diagnostic accuracy of mpMRI for previously negative patients with sensitivities of 78-100%, specificities of 30-100%, PPVs of 36-100%, and NPVs of 69-100%. 18,19,25,[27][28][29]37 -The overall improvement in csPCa detection rate for the 15 studies comparing mpMRI-TB alone to TRUS-SB was 5% (95% CI 3-7, p<0.0001), with a reduction of cisPCa detection of 7% (95% CI 4-9, p<0.00001). -The overall improvement in csPCa detection for the five cohort studies comparing mpMRI-TB plus TRUS-SB to mpMRI-TB alone was 5% (95% CI 2-8, p=0.0005).…”
Section: Key Evidence For Recommendationmentioning
confidence: 96%
“…Twenty-two trials (all full-text publications) compared mpMRI with a reference standard (n=7) or with TRUS-SB (n=15) for previously negative men. The certainty of the aggregate study evidence for each comparison showed 15 of the 22 studies to be at either low, 8,10,15,37 , moderate, 7,12,16,21,22,25 or unclear 17,19,[27][28][29] risk of bias based on a GRADE approach. 48 -Seven studies reported on the diagnostic accuracy of mpMRI for previously negative patients with sensitivities of 78-100%, specificities of 30-100%, PPVs of 36-100%, and NPVs of 69-100%.…”
Section: Key Evidence For Recommendationmentioning
confidence: 99%